Interaksi Sufisme, Ekologi dan Teologi di Era Postmodernisme: Antara wahdat al-wujûd Ibn ‘Arabi dan sûluk al-Ghazali - Muhammad Iqbal; Muhammad Rusydi; Restu Aulad Al-Fattaah (Pascasarjana UIN ANTASARI Banjarmasin, 2023)
The era of postmodernism is an emerging reaction to the failure of the modern era, because the progress caused by the rationality of the modern era has brought many problems that are no less complicated for the generations that follow. The presence of Sufism is considered to be able to be a problem to solve this long problem, especially among Muslims. In order for Sufism to become more established in dealing with and solving these various problems, Sufism needs to develop and integrate with other scientific domains which in the context of this paper are ecology and theology. This paper seeks to present Sufism that integrates with ecology which is then called ecosufism which is referred to by Hossein Nasr. Meanwhile, this effort to integrate with theology is referred to the thought of Zurkani Jahja who placed Sufism as a methodology to reach the level of true adherents of the Islamic creed. Through this paper, a spirit can be found that seeks to restore awareness of the great potential that Muslims actually have if they are able to live their creed teachings correctly, and the only way that is considered to be able to lead to this passion is Sufism.